Problems of Using Gadgets in Learning for Islamic Education Students - Lailatul Badriyah; Moh Misbakul Mustofa; Ahmad Ridho Amir; M. Izzudin (International Journal Labs, 2026)
The widespread adoption of digital devices has transformed the learning habits of university students, including those studying in the Islamic Religious Education (PAI) program. This study was conducted to explore the issues arising from gadget utilization among PAI students in higher education settings. A qualitative descriptive design was employed, with data collected through observations and in-depth interviews. To ensure the credibility of the findings, data triangulation techniques were applied. The results demonstrate that students spend approximately 5–8 hours per day using gadgets, a duration that exceeds recommended levels of use. Despite the extensive amount of time devoted to these devices, only a small proportion around 30% is directed toward educational and academic activities. In addition, the findings reveal a growing dependence on artificial intelligence (AI) technologies in the learning process. Such dependence may weaken students' intellectual engagement and reduce opportunities to develop independent reasoning and critical thinking skills. The increasing preference for AI-generated solutions, whose accuracy and reliability may not always be fully verified, encourages a more convenient but less reflective approach to learning. Consequently, this trend poses challenges to the cultivation of analytical, investigative, and higher-order thinking abilities that are fundamental to academic development, particularly within the discipline of Islamic Religious Education.